A new synthetic method toward a key intermediate in the total synthesis of alkannin and shikonin. Issue 9 (September 2021) - Zheng, Xiaogang; Hu, Hang; Xu, Defeng
In the present work, a new synthetic method toward a key intermediate in the total synthesis of alkannin and shikonin is developed. The key intermediate, 4-methyl-1-(naphtho[1, 8- de :4, 5- d'e' ]bis([1, 3]dioxine)-4-yl)pent-3-en-1-one (5 ), is synthesized via the reaction of 1, 8:4, 5-bis(methylenedioxy)naphthalene-2-carboxylic acid N -methoxy- N -methylamide with prenyllithium. This synthetic approach avoids the use of N -methoxy- N, 4-dimethylpent-3-enamide, which is not easy to obtain, and the toxic reagent sodium cyanide.